2003
DOI: 10.1038/sj.onc.1206415
|View full text |Cite
|
Sign up to set email alerts
|

Beta-catenin expression in Dupuytren's disease: potential role for cell–matrix interactions in modulating beta-catenin levels in vivo and in vitro

Abstract: Dupuytren's disease (DD) is a superficial fibromatosis of the hand. Although the molecular mechanisms responsible for this disease are unknown, recent studies suggest that beta-catenin may be a key factor involved in fibromatosis. In this study, we analysed the in vivo and in vitro expression levels of beta-catenin in DD, using surgical specimens and primary cell lines. Although no somatic mutations (exon 3) of beta-catenin were detected, Western blot analysis revealed high levels of beta-catenin in diseased p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
58
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 41 publications
4
58
1
Order By: Relevance
“…Within this pathway, β-catenin is a key signaling molecule regulated by Wnt whose expression is dysregulated in DD. 26,27 Currently, it is unknown how the SNPs affect gene expression within the Wnt pathway. One study demonstrated down-regulation of Wnt11 in surgically removed tissue, 28 and another study demonstrated an increase in Wnt5a, 26 with a third study demonstrating that the microRNA profile in DD is altered, including that for Wnt5a.…”
Section: Discussionmentioning
confidence: 99%
“…Within this pathway, β-catenin is a key signaling molecule regulated by Wnt whose expression is dysregulated in DD. 26,27 Currently, it is unknown how the SNPs affect gene expression within the Wnt pathway. One study demonstrated down-regulation of Wnt11 in surgically removed tissue, 28 and another study demonstrated an increase in Wnt5a, 26 with a third study demonstrating that the microRNA profile in DD is altered, including that for Wnt5a.…”
Section: Discussionmentioning
confidence: 99%
“…Increased β-catenin accumulation [17,19] and IGF2 expression [18] have been previously identi ed in DD tissue and primary broblasts compared with controls from adjacent, phenotypically non-brotic palmar fascia. As FSS and DD are clinically associated [3,20], we were interested to see if these characteristics were common to both connective tissue broses.…”
Section: Discussionmentioning
confidence: 99%
“…Forsman et al 10 associated the upregulation of ROR2 with Dupuytren's contracture pathogenesis for the first time, using the geneexpression data reanalyzed in this study. The catenin (cadherin-associated protein) b-1 (CTNNB1 GeneID: 1499), which has been implicated in Dupuytren's contracture, 27 is the target gene of several miRNAs, but its mRNA-expression level is not altered compared with that of control samples.…”
mentioning
confidence: 99%
“…26 Elevated levels of b-catenin have been reported in Dupuytren's contracture without involvement of b-catenin mutations. 27 Possible mechanisms explaining b-catenin accumulation include alterations in the Wnt/b-catenin signaling pathway, which makes it potentially the most important pathway involved in Dupuytren's contracture pathogenesis. This pathway is activated in the wound-healing process, recruiting proliferating fibroblasts to form a collagen matrix, 28 and it has an important function in regulating fibroblast proliferation and cell fate in various fibrous tumors.…”
mentioning
confidence: 99%